Assessment of Diversity and Fidelity of Transmission of Streptococcus mutans Genotypes in American Indian and Southeast Iowa Mother-Child Dyads - Alissa Villhauer; David Lynch; John Warren; David Drake (Frontiers Media S.A., 2022)
Early childhood caries (ECC) is a common chronic infectious disease of childhood with a complex etiology and many contributing risk factors. Its prevalence is greater in certain racial and ethnic minority groups and populations with low socioeconomic status. Among the species of bacteria that contribute to the progression of dental caries, Streptococcus mutans (SM) has long been considered a primary etiological agent of the disease. We report here on the genotypic diversity, commonality, and fidelity of mother-child transmission of S. mutans in mother-child dyads in two high-risk populations.MethodsThirty-eight mother-child dyads from a Southeast Iowa population and 40 dyads from a Northern Plains American Indian Tribe were selected for a comparison of S. mutans genotype profiles within and between populations. S. mutans was isolated from whole mouth plaque samples collected from each subject. DNA was extracted and AP-PCR using OPA2 primer was performed. Amplified DNA was electrophoresed and images of the resulting patterns were compared via GelCompar®IIv6.5 software.ResultsThirty unique S. mutans genotypes were identified from the 1,638 S. mutans isolates analyzed. Fifteen genotypes (50%) were seen in both cohorts, while 11 were unique to the American Indian (AI) cohort and 4 were unique to the Southeast Iowa (SEI) population. Within the AI cohort, 61.5% (16/26) of the S. mutans genotypes identified were seen in ≥2 individuals and 14 of the 26 (53.8%) were seen in ≥2 dyads. In the SEI cohort, 78.9% (15/19) of the S. mutans genotypes identified were seen in ≥2 individuals and 13 of the 19 (68.4%) were present in ≥2 dyads. Fifty-seven percent of AI children and 23% of SEI children displayed fidelity of mother-child transmission of ≥1 S. mutans genotype.ConclusionIn comparing the populations, we observed large variation in genotypic diversity and fidelity of mother-child transmission, while the amount of commonality seen in both cohorts was similarly high in both groups. This study furthers our understanding of the genotypic diversity of S. mutans in both of these populations and provides a basis for further comparison to other populations at greater risk for developing ECC.